“Strange Sights and Sounds”: Indirection and the Rhetoric of the Feminine in Mary E. Wilkins Freeman’s Tales (1852-1930) - Audrey Fogels (Transatlantica)
The following article analyzes the ways in which nineteenth-century regional writer Mary E. Wilkins Freeman (1852-1930) composes supernatural tales that address in a very indirect fashion disturbing issues such as child abuse, domestic violence and frustrated female desires. In her gothic-like domestic tales, the climax of revelation is indeed continually deferred, as if the female storyteller could simply not tell her secret. Such a rhetoric of indirection becomes all the more intricate as these stories are haunted by spectral but authoritarian male figures whose presence both facilitates and blocks the possibility of revelation. This results in the production of ever-elusive meanings, in which the interaction between the masculine and the feminine plays a key role. In the end, if trauma lies at the heart of Freeman’s texts, it can only be revealed indirectly, in a rhetoric that Freeman links to the feminine.